2007
DOI: 10.1074/jbc.m704551200
|View full text |Cite
|
Sign up to set email alerts
|

Uridylate-specific 3′–5′-Exoribonucleases Involved in Uridylate-deletion RNA Editing in Trypanosomatid Mitochondria

Abstract: In kinetoplastid protists, maturation of mitochondrial premRNAs involves the insertion and deletion of uridylates (Us) within coding regions, as specified by mitochondrial DNA-encoded guide RNAs. U-deletion editing involves endonucleolytic cleavage of the pre-mRNA at the editing site followed by U-specific 3-5-exonucleolytic removal of nonbase-paired Us prior to ligation of the two mRNA cleavage fragments. We showed previously that an exonuclease/endonuclease/phosphatase (EEP) motif protein from Leishmania maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 41 publications
2
43
1
Order By: Relevance
“…degrades synthetic ssRNA ending with Us (Aphasizhev and Simpson 2001). In agreement with the report that both REX1 and REX2 are active in vitro as U-specific exonucleases (Rogers et al 2007), this activity was indeed readily detectable in the MEAT1 complex (Fig. 6C).…”
Section: Editosome-like Particle Catalyzes Guided U-insertion and Mrnsupporting
confidence: 77%
See 2 more Smart Citations
“…degrades synthetic ssRNA ending with Us (Aphasizhev and Simpson 2001). In agreement with the report that both REX1 and REX2 are active in vitro as U-specific exonucleases (Rogers et al 2007), this activity was indeed readily detectable in the MEAT1 complex (Fig. 6C).…”
Section: Editosome-like Particle Catalyzes Guided U-insertion and Mrnsupporting
confidence: 77%
“…Although the resultant phenotypes and effects on editing in vivo varied considerably, to our knowledge only REL2 (Gao and Simpson 2003;O'Hearn et al 2003) and REX2 (Rogers et al 2007) knockdowns had no effect on T. brucei viability. Puzzled by the apparently intact editing process but inhibited cell growth in MEAT1-depleted cells, we developed a functional RNAi knock-in system to address the questions of possible RNAi off-targeting and whether MEAT1's enzymatic activity is responsible for the observed phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7), and Schnaufer et al (2003) observed active precleaved U-deletion from protein associations that contain minimal TbMP42. Furthermore, TbMP99 Worthey et al 2003) and/or TbMP100 Rogers et al 2007) have been reported to be enzymes catalyzing the 39-U-exo activity of U-deletion. Nonetheless, editing could utilize another 39-U-exo activity.…”
Section: Tbmp42 Is Needed Formentioning
confidence: 99%
“…The U-deletional and U-insertional cleavage steps are catalyzed by TbMP90/KREN1 and TbMP61/ KREN2, respectively Trotter et al 2005;Kang et al 2006) (or by TbMP67/KREPB2/KREN3 for the U-insertion that uses a cis-located gRNA; Carnes et al 2008), although it has additionally been inferred that TbMP42/KREPA3/band VI may catalyze editing endonucleolytic cleavage (Brecht et al 2005). The U-removal step is catalyzed by TbMP100/KREX1 (Worthey et al 2003;Kang et al 2005) and TbMP99/KREPC2/KREX2/band I Worthey et al 2003;Rogers et al 2007) and/or possibly TbMP42/KREPA3/band VI (Brecht et al 2005); the U-addition step is catalyzed by the TbMP57/KRET2 TUTase (Aphasizhev et al 2003c;Ernst et al 2003). Finally, the ligation steps are catalyzed by the TbMP52/KREL1/band IV and TbMP48/KREL2/band V RNA ligases (Rusche et al 1997(Rusche et al , 2001Schnaufer et al 2001; see also Sabatini and Hajduk 1995;McManus et al 2001), which preferentially seal in U-deletion and Uinsertion, respectively Cruz-Reyes et al 2002;Schnaufer et al 2003; see also Gao and Simpson 2003).…”
Section: Introductionmentioning
confidence: 99%